A novel vaccine designing method using in-silico tools against scaffold protein OPG 125 of monkeypox virus - Jannati, Sadia Zafur (Brac University, 2024)
A thesis submitted to the School of Pharmacy in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2024.